Interrogating Bishwas: Reimagining a Christian Neighbourhood in Kolkata, India - Dasgupta, A. (University of jaffna, 2024)
It is often argued that theology and anthropology share an ‘awkward relationship.’ To analyse the relation between the two, this paper explores the everyday lives of the Christians residing in a Bengali Christian neighbourhood in Kolkata, termed here as the larger Christian para (para meaning neighbourhood in Bengali). Through ethnographic fieldwork conducted in various phases, the paper discerns how various Christians across denominations – Protestants, Catholics and Pentecostals implicate the role of bishwas (faith and belief ) in their interpersonal neighbourhood relations. The paper attempts to capture the role of bishwas in producing, transforming and revising the meaning of ‘neighbourhood’ and ‘neighbours’ and puts forward the argument of the neighbourhood as a theological project. By interrogating and interpreting bishwas through everyday theological discussions and reflections, the paper examines the similarities and differences in bishwas shared by the different denominations in their understanding of the neighbourhood. Borrowing from the literature of bishwas (both faith and belief ), the paper reads and analyses the link between bishwas to the place of living. How do bishwas help in imagining a neighbourhood beyond socio-spatial boundaries? How do biblical narratives and examples help us to rethink the categories of ‘neighbours’ and ‘neighbourhood’ in a multicultural south Asian city like Kolkata? At the same time, the divisions and fissures are seen among Protestants and Catholics and also among native Bengali Protestants and non-native Protestant pastors, which informs us about the complexity of bishwas in constituting the neighbourhood as theological project. By attempting to answer such complexities, the idea of the neighbourhood as a theological project is put forward.
Keywords: Role of bishwas; Theology of neighbourhood; Intersectionality of denominational faith